A Review on Viral Encephalitis- - Al-bayaa, Yasmeen J.; Kadhim, shaimaa J.; Hamid, Zainab A. (Journal of the Faculty of Medicine Baghdad, 2022)
Background: Inflammation of the brain parenchyma brought on by a virus is known as viral encephalitis. It coexists frequently with viral meningitis and is the most prevalent kind of encephalitis.Objectives: To throw light on viral encephalitis, its types, epidemiology, symptoms and complications.Results: Although it can affect people of all ages, viral infections are the most prevalent cause of viral encephalitis, which is typically seen in young children and old people. Arboviruses, rhabdoviruses, enteroviruses, herpesviruses, retroviruses, orthomyxoviruses, orthopneumoviruses, and coronaviruses are just a few of the viruses that have been known to cause encephalitis.Conclusion: As new viruses emerge, diagnostic techniques advance, or we learn more about the pathophysiology of the disease, viral encephalitis has become a more serious public health concern.